2011
DOI: 10.1063/1.3556455
|View full text |Cite
|
Sign up to set email alerts
|

Tunable vibrational band gaps in one-dimensional diatomic granular crystals with three-particle unit cells

Abstract: We investigate the tunable vibration filtering properties of one-dimensional diatomic granular crystals composed of arrays of stainless steel spheres and cylinders interacting via Hertzian contact. The arrays consist of periodically repeated three-particle unit cells (steel-cylinder-sphere) in which the length of the cylinder is varied systematically. We apply static compression to linearize the dynamic response of the crystals and characterize their linear frequency spectrum. We find good agreement between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 33 publications
1
77
0
Order By: Relevance
“…Granular crystals have been proposed for a variety of engineering applications; some of these include shock energy trapping [4][5][6], vibration filtering [7,8], focusing [9], energy harvesting [10], and nonlinear localization [11]. In addition, granular crystals have been shown to support metastable breathers in material systems characterized as "sonic vacuum" [12], and localized oscillations in diatomic crystals [13] and in systems with defects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Granular crystals have been proposed for a variety of engineering applications; some of these include shock energy trapping [4][5][6], vibration filtering [7,8], focusing [9], energy harvesting [10], and nonlinear localization [11]. In addition, granular crystals have been shown to support metastable breathers in material systems characterized as "sonic vacuum" [12], and localized oscillations in diatomic crystals [13] and in systems with defects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to design tunable materials, it has been shown that Braggtype bandgaps can be controlled through changes in the periodic modulation of impedance mismatch within the medium [7][8][9] , while in locally resonant metamaterials tuning of functionalities is typically achieved by controlling the natural frequency of the resonating units 5,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the experimental data with the numerics, we find an upshift of 5%-10%, similar to the upshift observed in Refs. [17,30]. For the r = 5.56 mm defect, the average experimental defect-mode frequency is f Possible reasons for these upshifts have been identified in Refs.…”
mentioning
confidence: 99%
“…For the r = 5.56 mm defect, the average experimental defect-mode frequency is f Possible reasons for these upshifts have been identified in Refs. [17,30] and the references therein, such as error in the material parameters, nonlinear elasticity, surface roughness, dissipative mechanisms, and misalignment of the particles. Nevertheless, it is clear from Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation